Population dynamics of Antarctophthirus microchir (Anoplura: Echinophthiriidae) in pups from South American sea lion, Otaria flavescens, in Northern Patagonia - Aznar Avendaño, Francisco Javier; Leonardi, María Soledad; Beron Vera, Barbara; Vales, Damián Gustavo; Ameghino, Santiago Pedro; Raga, J. A.; Crespo, Enrique Alberto (Parasitology)
We analysed population dynamics of the louse Antarctophthirus microchir in pups of the South American sea lion, Otaria flavescens, at the Punta León rookery (Argentina) over a period of 2 years. A total of 136 pups were aged and marked at the beginning of the lactation period ashore, then sampled for lice at different times within 30 days. Sampling was restricted to the chest and belly, two sites where lice were especially abundant. This concentration on ventral areas might protect lice from thermal stress in the austral summer. Infestation patterns in pups ≤3 days old suggested that the potential for transmission increased from first nymphs to adults. Population trends of each instar with pup age, based on standardised values of abundance, were conserved between years, reflecting the basic dynamics of recruitment and reproduction. However, trends based on log-transformed abundances varied significantly between years; apparently, environmental conditions affected growth of lice populations differently each year. Stage-based deterministic models for population growth of A. microchir suggested generation times from 18 to 23 days. Accordingly, only 2 lice generations might be produced before pups start going to the sea. Shortening the cycle to accommodate a third generation might be risky, whereas a 2-generation cycle might at least result in larger females producing higher numbers of viable offspring. Fil: Aznar Avendaño, Francisco Javier. Institut Cavanilles de Biodiversitat I Biologia Evolutiva; Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Beron Vera, Barbara. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Vales, Damián Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Ameghino, Santiago Pedro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: ...